Mengenal Sistem Administrasi Perpajakan Modern di Era Reformasi Perpajakan - Rahman, Abdul (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2009)
tax reform application period in Indonesia is not only held in 1985 but also continued by tax reform in organization section of tax directorate general. Basically, tax administration reform executed by Tax Directorate General in 1985, 1994, 1997, and 2000, in fact, it has no been changed to make simpler of organization structure but just adding sections and sub sections.